Unlocking heirloom diversity: a pathway to bridging global challenges in modern apple cultivation - Aoun, Mirella (Frontiers in Horticulture, 2024)
Reports indicate that climate changes will result in the extinction of a significant percentage of plant species even though many of these species contributed to crucial genetic traits that led to the domestic crop development. In the past, the diversified range of plant species, varieties, and agricultural practices has allowed the agriculture production and local food systems to tolerate moderate climate variability. Today, industrial farming relies on a very limited genetic diversity for commercial production. Narrowing the genetic base leads to higher susceptibility to environmental changes and diseases.Heirloom cultivars survived climate variations and extreme conditions, but were abandoned in favor of a handful of commercial cultivars that dominate the food industry and fit the standards of the global food system. From a climate change perspective, it would be important to conserve heirloom cultivars to preserve biodiversity and make a greater genetic diversity available to farming which will lead to resilience and adaptation.